Propaganda and disinformation: Ukrainian response to Russian aggression - Pronoza, Inna (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
The issue of Ukraine’s resistance to Russian propaganda has been thoroughly examined. Various strategies employed by the Ukrainian government and society to counter disinformation from Russia have been revealed. The impact of Russian propaganda on public opinion has been investigated, highlighting key methods such as the dissemination of fake news, emotional manipulation, and the creation of a hostile image.